The effect of FeCl3 on the optical constants and optical band gap of MBZMA-co-MMA polymer thin films - Yakuphanoğlu, Fahrettin; Barim, G.; Erol, I. (Elsevier Science Bv, 2007)
The effects of the FeCl3 dopant on the optical constants and optical band gap of the methylbenzyl methacrylate (MBZMA)-co-methyl-methacrylate (MMA) polymer thin films have been investigated by the optical characterization. The optical constants of the thin films are changed with FeCl3 dopant. The refractive index dispersion curves of the thin films are fitted by Cauchy-Sellmeier model and dispersion parameters (a(1) and n(0)) change with FeCl3 dopant. The magnitude of the refractive index increases with increasing FeCl3 dopant. The electric susceptibility of the thin film materials was calculated and the electric susceptibility increases with FeCl3 content. The optical band gap values of the thin films were determined. The obtained band gap values are decreased with FeCl3 dopant. The FeCl3 dopant changes the width of localized states in the optical band gaps of the thin films. The optical band E-g of the thin films changes from 3.52 to 3.05 eV with increasing FeCl3 dopant, while the width of localized states in optical band gap changes from 1101.47 to 596.3 meV. It is concluded that the optical constants and optical band gap of the MBZMA-co-MMA polymer thin films change by the FeCl3 dopant. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: optical constant; polymer; optical band gap; thin film